Traditional Market Merchant Attitudes in the Perspective of Islamic Business Ethics - Tjiptohadi Sawarjuwono, Purnama Putra, (Opción, 2019)
This research employs phenomenology to elicit the behaviors of merchants in the traditional market using the perspective of Islamic business ethics via comparative qualitative research methods. The research result shows that the behavior of the merchants at the Pasar Baru Kota Bekasi shaped by the principles of Islamic business ethics including tauhid (the divine oneness of God), equilibrium, free will, responsibility, and Ihsan. In conclusion, being wise can be implemented also by giving extra time for payment to the customers and giving bonuses to them.